The origins of Nazi genocide : from euthanasia to the final solution - Friedlander, Henry, 1930-2012 (University of North Carolina Press, 1995)
Henry Friedlander explores in chilling detail how the Nazi program of secretly exterminating the handicapped and disabled evolved into the systematic destruction of Jews and Gypsies. Tracing the rise of racist and eugenic ideologies in Germany, he describes how the so-called euthanasia of the handicapped provided a practical model for mass murder, thereby initiating the Holocaust. Based on extensive research in American, German, and Austrian archives as well as Allied and German court records, the book also analyzes the involvement of the German bureaucracy and judiciary, the participation of physicians and scientists, the motives of the killers, and the nature of popular opposition. Friedlander also sheds light on the special plight of handicapped Jews, who were the first singled out for murder.